FACTORS AFFECTING POST-CORONARY ANGIOGRAPHY/PCI PATIENT CARE COMPLIANCE AT RSUD ULIN BANJARMASIN - Wasila, Hardi; Solikin, Solikin; Olviani, Yurida (STIKES Suaka Insan, 2024)
Acute Coronary Syndrome (ACS) is a collection of symptoms characterized by the blockage of coronary arteries in the heart, where the supply of oxygen-rich blood and nutrients to the heart muscle is partially or completely obstructed. The World Health Organization (WHO) states that ACS is a global issue. The non-surgical intervention management for ACS patients is coronary angiography/PCI. Patients post-coronary angiography/PCI often experience rehospitalization at Ulin General Hospital due to non-compliance with post-procedure care. This study aims to identify the factors influencing the compliance of post-coronary angiography/PCI patients in their care at Ulin General Hospital Banjarmasin, using a cross-sectional descriptive analysis research design on 30 respondents with purposive sampling technique. The results of the Spearman's rho correlation statistical test showed that the motivation factor (p-value = 0.003) is the only factor with a significant influence, a strong correlation, and a positive relationship with compliance in post-coronary angiography/PCI care at Ulin General Hospital Banjarmasin. This study serves as a reference for further development integrated with other factors, beyond those presented, according to the concept of post-coronary angiography/PCI patient care.